18F-FDG PET/CT Imaging of Boari Flap Mimicking Urothelial Cancer Recurrence - Fishberg, Sharon E.; Gofrit, Ofer N.; Orevi, Marina (World Journal of Nuclear Medicine, 2022)
A 63-year-old man underwent distal ureterectomy as a treatment for urothelial carcinoma of the ureter. Reconstruction of the urinary system was accomplished by tubularizing part of the bladder roof (Boari flap). A year later, metastatic evaluation with 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) showed high metabolic activity in the reconstructed area. Thorough evaluation confirmed the presence of a bladder diverticulum (the Boari flap) with no evidence of malignancy. We present the first 18F-FDG PET/CT images of a Boari flap in the literature.
Keywords: 18F-FDG PET/CT; Boari flap; local recurrence